ISOLATION OF ANTIFUNGI BACTERIA FROM BANANA RHIZOSPHERE TO INHIBIT Fusarium Oxysproum f.sp cubense (FOC) GROWTH - Albert Sembiring; Natalia Lusianingsih Sumanto (JBIO: jurnal biosains (the journal of biosciences), 2019)
Fusarium wilt disease on banana has been known as panama disease one of the main diseases that cause huge losses for banana farmers. It is caused by the soil-borne fungal pathogen, Fusarium oxysporum f.sp cubense (Foc), which is very hard control because it is saprophytic in the soil. The mold infiltrates the root to vascular tissue that induces yellowing on the leaf, so this pathogen can attack the root, stem dan leaf. The research aimed to search bacteria from the banana rhizosphere that have an antifungal activity to inhibit Foc growth. Bacteria was isolated by serial dilution then was spread on King’s B agar medium incubation 28oC (room temperature). Four quadrants in vitro test on PDA medium used twenty bacterial from isolation, from the test was obtained six isolates have the potential to inhibit the growth of Foc. Based on percentage inhibition radial growth four isolates that have inhibition 50% over which TR2 was the highest at 79.07%. The in vitro test confirmed that bacteria from the banana rhizosphere have potential as biocontrol agent because it was able to inhibit the Foc growth.